Antigen-specific and non-specific helper activities derived from supernatants of human influenza virus-specific T-cell lines. - Zanders, E; Fischer, A; Smith, S; Beverley, P; Feldmann, M (1983)
A T-cell line (H3) was established by culturing human peripheral blood mononuclear cells with influenza virus A/X31 and maintained in long term culture with Interleukin-2 (TCGF). Supernatants were prepared by culturing these cells overnight in the absence of Interleukin-2 but with A/X31 and irradiated autologous E rosette negative cells as a source of antigen presenting cells, and harvesting by centrifugation. The supernatants were shown to replace T cells in helping E- (B) cells to produce antibody specific to A/X31 which was measured by enzyme immunoassay (EIA). Although maximal help was obtained with autologous or semi allogeneic B cells (in the latter case bearing HLA-DR 3 loci) there was still significant antibody production with allogeneic combinations. The supernatants were subsequently fractionated into specific and non-specific helper activities by gel filtration, giving an approximate mol. wt of 50-70,000 and 10-30,000 for each respectively. The specific HF was shown to be genetically restricted in its action upon B cells and also to generate antibody to A/X31 only. The lower molecular weight material acted on any responding B cell regardless of HLA-DR type and produced antibody non-specifically in culture with E- cells even in the absence of antigen. The apparent lack of restriction was therefore due to the masking effect of non-specific and non-restricted HF(s) on the genetically restricted specific HF produced by this line.